Magnetic ion-exchange resin treatment: Impact of water type and resin use - Mergen, Maxime Rodolphe Denis; Jefferson, Bruce; Parsons, Simon A.; Jarvis, Peter (Elsevier Science B.V., Amsterdam., 2008)
Three raw waters of fundamentally different natural organic matter (NOM) character were treated by magnetic resin using a bench-scale method designed to mimic how the resin is used in continuous operation. Increasing water hydrophobicity resulted in reduced dissolved organic carbon (DOC) removal with removal of 56%, 33% and 25% for waters containing 21%, 50% and 75% hydrophobic NOM, respectively. Study of consecutive resin uses showed that the NOM in the hydrophobic water had high affinity for the resin shown by DOC removal of 65% after the first use of the resin. This dropped to 25% DOC removal after 15 consecutive resin uses. For the more hydrophilic waters, NOM removal remained consistent after each resin use. The hydrophobic sample contained higher MW NOM that was capable of blocking resin sites that prevented continual adsorption of organics on to the resin. The hydrophilic NOM containing a large proportion of hydrophilic acids was consistently removed to around 60%. The water containing algogenic-derived NOM was poorly removed by magnetic resin. Subsequent coagulation showed higher removal with increasing hydrophobicity. (C) 2007 Elsevier Ltd, All rights reserved.
Keywords: algogenic coagulation hydrophilic hydrophobic magnetic ion-exchange resin MIEX natural organic matter natural organic-matter content surface-water bromate formation removal coagulation disinfection carbon pretreatment combination precursors